2021
DOI: 10.1159/000516361
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 1, but Not Insulin-Like Growth Factor-Binding Protein 3, Predicts Central Precocious Puberty in Girls 6–8 Years Old: A Retrospective Study

Abstract: <b><i>Background:</i></b> Central precocious puberty (CPP) in females is characterized by thelarche before 8 years of age. Evidence of reproductive axis activation confirms the diagnosis (basal serum luteinizing hormone (LH) ≥0.3 IU/L or LH-releasing hormone (LHRH)-stimulated LH ≥5 IU/L). Stimulation testing is the diagnostic gold standard but is time-consuming and costly. Serum levels of insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-binding protein 3 (IGFBP-3) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This study found that the IGF-1 of girls in the RP-CPP group was higher than that in the SP-CPP group. This study also found that in the RP-CPP group, the IGF-1 was positively correlated with the classical CPP parameter LH, which was consistent with the results of Escagedo et al [3] . On the one hand, IGF-1 plays a role in inducing the proliferation of chondrocytes and osteoblasts to regulate linear growth in the process of human puberty, on the other hand, it can also regulate the HPG axis by regulating the central nervous system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found that the IGF-1 of girls in the RP-CPP group was higher than that in the SP-CPP group. This study also found that in the RP-CPP group, the IGF-1 was positively correlated with the classical CPP parameter LH, which was consistent with the results of Escagedo et al [3] . On the one hand, IGF-1 plays a role in inducing the proliferation of chondrocytes and osteoblasts to regulate linear growth in the process of human puberty, on the other hand, it can also regulate the HPG axis by regulating the central nervous system.…”
Section: Discussionsupporting
confidence: 92%
“…Puberty development is regulated by the GH-IGF-1 axis and HPGA. Activation of the HPG axis promoted the secretion of GH and IGF-1, and estrogen further promoted the secretion of GH, resulting in increased concentrations and enhanced effects of IGF-1 in the growth plate [3] . Studies have found that IGF-1 stimulates a peptidergic pathway within the medial basal hypothalamus (MBH) to eliminate the inhibition of GnRH secretion before puberty, and IGF-1 seems to play a role in activating and enhancing GnRH secretion during puberty [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to find the core proteins that are linked to CPP, the top 25 proteins with connectivity were selected to construct a PPI network and IGF-1 was found to have the highest connectivity. IGF-1 has been previously shown to have a predictive role as a biomarker in the diagnosis of girls with CPP ( 27 ). IGF2 and IGFBP1 were also thought to be involved in the process of puberty ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%